Mapping Soft Computing Concepts and Research Trends in Computer Vision through Bibliometric Analysis Using VOSviewer and Publish or Perish - Damayanti, Aldiana (Jurnal Informatika dan Sains Media (JISMA), 2024)
The background of this research is the significant increase in the number of scientific publications related to the use of soft computing in computer vision in recent years. As bibliometric data becomes increasingly complex, there is a need for effective tools to map and analyze such data. This study aims to analyze and demonstrate the steps of bibliometric data analysis using VOSViewer in a comprehensive and systematic manner. The method used in this research is to conduct bibliometric analysis to produce visualization of collaboration network maps and collaboration density maps. The analysis was carried out on a total of 200 documents obtained with predetermined topics for the period 2017-2021. Through network visualization, it can be seen that the research development map in the field of deep learning is divided into 4 clusters. Cluster One consists of 12 topics, Cluster Two consists of 12 topics, Cluster Three consists of 5 topics, and Cluster Four consists of 4 topics. The research conclusion show that VOSViewer can be used to provide recommendations in data analysis results. This research provides a comprehensive and systematic guide for new users of VOSViewer to conduct bibliometric data analysis and effectively present visualizations of research developments in the field of deep learning.